Social welfare and wage inequality in search equilibrium with personal contacts - Anna Zaharieva (Bielefeld University, Institute of Mathematical Economics (IMW), 2011)
This paper incorporates job search through personal contacts into an equilibrium matching model with a segregated labour market. Job search in the public submarket is competitive which is in contrast with the bargaining nature of wages in the informal job market. Moreover, the social capital of unemployed workers is endogenous depending on the employment status of their contacts. This paper shows that the traditional Hosios (1990) condition continues to hold in an economy with family contacts but it fails to provide efficiency in an economy with weak ties. This inefficiency is explained by a network externality: weak ties yield higher wages in the informal submarket than family contacts. Furthermore, the spillovers between the two submarkets imply that wage premiums associated with personal contacts lead to higher wages paid to unemployed workers with low social capital but the probability to find a job for those workers is below the optimal level.
urn:nbn:de:0070-pub-26717052
Keywords: J23; J31; J64; D10; 330; Personal contacts; family job search; social capital; wages; equilibrium efficiency; Arbeitsuche; Social Capital; Lohnstruktur; Arbeitsmarkt; Matching; Gleichgewicht; Theorie